Generation of induced pluripotent stem cell lines TRNDi037-A and TRNDi038-A from two patients with Alagille syndrome carrying heterozygous JAG1 mutations - Elena F. Evans; Guibin Chen; Ivan Pavlinov; Xiuli Huang; Kaari Linask; Chengyu Liu; Alexander Rodriguez Lopez; Melissa A. Gilbert; Nancy B. Spinner; Steven Rodemse; Karsten Baumgärtele; Catherine Z. Chen; et al. (Stem Cell Research)
Human induced pluripotent stem cell (iPSC) lines TRNDi037-A and TRNDi038-A were generated from the lymphoblastoid cell lines (LCL) of two patients with different heterozygous JAG1 variants resulting in Alagille syndrome (ALGS). ALGS is a rare genetic disease of haploinsufficiency that affects the formation of the bile duct, in addition to other symptoms. These ALGS iPSC lines can be used to model ALGS and aid in the identification of therapeutics to treat patients with ALGS.